The effect of innovation and strategic planning on enhancing organizational performance of Dubai Police - Al-Dhaafri, Hassan Saleh (2020)
Purpose – The purpose of this study is to examine empirically the joint effect of innovation and strategic planning on organizational performance of Dubai Police. Design/methodology/approach – To examine the hypothesized model of the study, a survey questionnaire was used. The data were collected from the general department of total quality of the Dubai Police. The total number of questionnaires distributed was 150, out of which only 95 usable questionnaires were returned and ready for analysis. The regression approach through SPSS was used to analyze the data and test the hypotheses. Findings – The statistical results confirm the effect of strategic planning and innovation on the organizational performance of Dubai Police. Research limitations/implications – Further details and valuable implications are discussed throughout the study. The results have many practical implications, in that it can help managers to make proper decisions when deciding to implement innovation and strategic planning in their organizations. Originality/value – This study is a rare and unique empirical study that examines the effect of innovation and strategic planning on the organizational performance of Dubai Police